Study of the development of a low cost milkfish fry counter - Dela Cruz, Jennifer Chua (Animo Repository, 1997)
A low cost electronic milkfish fry counter for aqua - culture industry is developed in this study. The present manual method of counting was compared with the electronic counting device particularly the speed and accuracy. The study found out that electronic counter will expedite the counting of hundreds of fry than counting it manually using the scooping method. The accuracy of the counting device was also found to be higher than the normal method. Further, the designed counter can be used with other fry species other than milkfish fry.